Neutrophils in tumorigenesis: missing targets for successful next generation cancer therapies? - Tolle, Fabrice; Umansky, Viktor; Utikal, Jochen; Kreis, Stephanie; Bréchard, Sabrina (International journal of molecular sciences, 2021)
Neutrophils—once considered as simple killers of pathogens and unexciting for cancer research—are now acknowledged for their role in the process of tumorigenesis. Neutrophils are recruited to the tumor microenvironment where they turn into tumor-associated neutrophils (TANs), and are able to initiate and promote tumor progression and metastasis. Conversely, anti-tumorigenic properties of neutrophils have been documented, highlighting the versatile nature and high pleiotropic plasticity of these polymorphonuclear leukocytes (PMN-L). Here, we dissect the ambivalent roles of TANs in cancer and focus on selected functional aspects that could be therapeutic targets. Indeed, the critical point of targeting TAN functions lies in the fact that an immunosuppressive state could be induced, resulting in unwanted side effects. A deeper knowledge of the mechanisms linked to diverse TAN functions in different cancer types is necessary to define appropriate therapeutic strategies that are able to induce and maintain an anti-tumor microenvironment.
Gesehen am 30.09.2021